Cultural Regulation, Geographical Indication and the (re) Signification of an Artisanal Cheese - Almeida, Simone de Lira; de Paiva Júnior, Fernando Gomes; Guerra, José Roberto Ferreira; Medeiros, Janann Joslin (Organizações & Sociedade, 2021)
Laws and norms can change the production processes of an organization, with repercussions for the tangible and symbolic composition of its products. Based on this assumption of Cultural Studies, we seek to understand how the practice of cultural regulation by a group of small producers is (re)signifying the rennet cheese produced artisanally in the Agreste region of the Brazilian state of Pernambuco. We use discourse analysis to analyze interviews and documents such as the decrees and regulations that deal with processing dairy products in Brazil, as well as those governing the process of Geographical Indication, and compare the cultural meanings that have emerged in two spheres of regulation: the public and the private. Findings reveal governmental characterization of artisanal rennet cheese has been justified by a discourse of “quality” at both the state and federal levels. However, the regulation put in place in the private sphere of the Producers Association makes use of different arguments to construct the discourse of quality with respect to the same food.